1993
DOI: 10.1161/01.hyp.22.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of blood pressures in black and white children.

Abstract: The prevalence of hypertension is greater for blacks than whites. Whether black children have higher blood pressure than white children is less clear. We investigated this issue through a prospective longitudinal assessment of blood pressure in 345 white children and 164 black children. Each child had his or her blood pressure measured every 6 months for 2 to 5.5 years. The means for systolic and diastolic blood pressures for each individual were calculated, and the rate of change in blood pressure over time f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
2

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 27 publications
6
54
2
Order By: Relevance
“…Earlier puberty and weight gain in African American children may partly explain the difference in BP. 26 Given the higher overall risk of hypertension in African Americans compared with whites, the results from our study are consistent with other studies 1,3,25,26 suggesting that the excess burden of hypertension in African Americans may be due primarily to a higher BP level and rise in BP with age in adolescence and young adulthood. Efforts to prevent high BP and its sequelae in African Americans need to target groups before they reach middle age.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Earlier puberty and weight gain in African American children may partly explain the difference in BP. 26 Given the higher overall risk of hypertension in African Americans compared with whites, the results from our study are consistent with other studies 1,3,25,26 suggesting that the excess burden of hypertension in African Americans may be due primarily to a higher BP level and rise in BP with age in adolescence and young adulthood. Efforts to prevent high BP and its sequelae in African Americans need to target groups before they reach middle age.…”
Section: Discussionsupporting
confidence: 90%
“…24 -26 Manatunga and colleagues followed 164 African American and 345 white children for 2 to 5.5 years. 26 They found that the African American children had a significantly higher mean BP and rate of increase in BP over time. Earlier puberty and weight gain in African American children may partly explain the difference in BP.…”
Section: Discussionmentioning
confidence: 96%
“…[16][17][18][19][20] In some of these USA studies, ethnic differences in BP were still present after adjusting for age, weight, height, and BMI. 16,17 The UK result is still more unexpected in the face of a comparatively high BMI in African descent children. This finding of similar BP in children of African descent is consistent with the findings of similar BP levels in the younger African groups in the UK's adult studies.…”
Section: Children Of African Descentmentioning
confidence: 99%
“…19 For the amiloride study, members of the cohort were sent letters inviting them to participate. For the studies in which potassium excretion rates and serum potassium levels were measured, we used samples that had been collected from members of the cohort who had agreed to provide an overnight urine sample and a blood sample.…”
Section: Subjectsmentioning
confidence: 99%